PELATIHAN PENGENALAN MICROSOFT WORD SEBAGAI ALAT BANTU BELAJAR DI SMA IBRAHIMY 2 SUKOREJO - Siti Kholifah; Erinia Dzikrotul Kharimah; Zaehol Fatah (Jurnal Padamu Negeri, 2025)
Microsoft Word training in the field of education has a very important role in improving the competence of information and communication technology which can be called (ICT) in the field of Education. Microsoft Word is one of the most commonly used processing software to support the learning process, administration, and scientific writing. This training activity aims to provide basic to advanced understanding of Microsoft Word such as Document format setting, automatic table of contents creation in making papers, table processing, and insertion of images and graphics. The training method used is practical and interactive, so that can increase in participants ability to use Microsoft Word more effectively and efficiently in the context of Education. This training encourages digitalization in the school environment and increases productivity in the training and learning process.